Genetic diversity of vegetative and bunch traits of African oil palm (Elaeis guineensis) germplasm in India - P MURUGESAN; K L MARY RANI; D RAMAJAYAM; K SUNIL KUMAR; R K MATHUR; G RAVICHANDRAN; P NAVEEN KUMAR; V ARUNACHALAM (The Indian Journal of Agricultural Sciences, 2015)
Knowledge on genetic diversity among breeding materials could be an invaluable aid in oil palm (Elaeis guineensis Jacq.) improvement strategies. Germplasm from primary/secondary centres of origin were collected during 1994 under FAO programme and planted in the gene bank at DOPR Research Centre, Palode during 1998 were studied for genetic diversity. Twenty six accessions representing three African countries (Guinea Bissau, Tanzania and Zambia) were studied using 50 individual palms. Thirty numbers of vegetative and bunch component traits recorded during 2008 to 2013 were analysed in this study. An attempt was made using Shannon-Weaver Diversity Index (SWDI) with an objective to understand the level of diversity in these traits. In general, mean of all the accessions exhibited high levels (0.694) of diversity. Mean diversity estimate (0.778) was highest in Tanzanian source closely followed by Zambia (0.727) and least value (0.576) was observed in Guinea Bissau. Low diversity values (<0.32) for bunch weight, shell thickness, single fruit, and nut weight noticed in Guinea Bissau when compared to other sources. Highest level of homozygosity (SWD=0) for spine length was observed in Guinea Bissau population and similar trend of homzygosity noticed in other traits also in GB accessions. These findings combined with other evaluation results suggest that "Tanzanian population" possess adequate genetic variability that is potentially useful for oil palm improvement program in India. More palms should be preserved for populations that have higher diversity and those with rare traits.